2011
DOI: 10.1002/gepi.20566
|View full text |Cite
|
Sign up to set email alerts
|

Latent class model with familial dependence to address heterogeneity in complex diseases: adapting the approach to family-based association studies

Abstract: Clinical diagnoses of complex diseases may often encompass multiple genetically heterogeneous disorders. One way of dissecting this heterogeneity is to apply latent class (LC) analysis to measurements related to the diagnosis, such as detailed symptoms, to define more homogeneous disease sub-types, influenced by a smaller number of genes that will thus be more easily detectable. We have previously developed a LC model allowing dependence between the latent disease class status of relatives within families. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Loss of function mutations in the lysine-specific demethylase JARID1C , another gene of the JARID family, also causes syndromic intellectual disability (MIM 300534). In addition, two studies have shown association between JARID2 and ASDs, when using the data from the Autism Genetic Resource Exchange (AGRE) [38,39]. Based on these observations, we suggest that JARID2 is likely to be the critical gene within SRO I, and the main gene causing the neurodevelopmental syndrome in Patients 1–4.…”
Section: Discussionmentioning
confidence: 73%
“…Loss of function mutations in the lysine-specific demethylase JARID1C , another gene of the JARID family, also causes syndromic intellectual disability (MIM 300534). In addition, two studies have shown association between JARID2 and ASDs, when using the data from the Autism Genetic Resource Exchange (AGRE) [38,39]. Based on these observations, we suggest that JARID2 is likely to be the critical gene within SRO I, and the main gene causing the neurodevelopmental syndrome in Patients 1–4.…”
Section: Discussionmentioning
confidence: 73%
“…LCA is employed in the indications exploration, which can facilitate targeting future intervention resources to subgroups that promise to show the maximum treatment response (Bureau et al, 2011;Lanza and Rhoades, 2011). Traditionally, subgroup analysis aims to determine whether individuals respond differently to a treatment based on one or more measured characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, information describing each latent class provided an interpretation of the three classes while the probability of being in each class was employed as the phenotype in analysis. This approach avoids multiple pairwise comparisons of the three classes in analyses, avoids misclassification inherent in assigning individuals to a particular latent class, maximizes the number of subjects, and was shown previously to improve power to detect genetic association (Bureau et al, 2011). …”
Section: Methodsmentioning
confidence: 99%